Stimulation of inflammatory response in chicken Sertoli cells following metformin exposure - Michailidis, G; Giannenas, I (Journal of the Hellenic Veterinary Medical Society, 2024)
The testis is considered as an immune-privileged site, and testicular Sertoli cells have been identified as key players for conferring this immune privilege. These cells play an important physiological role in the testis, as they support, nourish and protect the germ cells, and present immune properties such as immune factors secretion, phagocytosis and constitute also the blood testicular barrier which limit damage to germ cells. The aim of the present study was to evaluate the inflammatory response in chicken Sertoli cells induced by metformin, an insulin-sensitizer drug which also possess anti-inflammatory properties, by studying the expression pattern of innate immune-related genes, including Toll-like receptors (TLRs), and cytokines, after a kinetic stimulation (0 to 48 hours) by metabolic dysregulation metformin induced. Chicken Sertoli cells were exposed to lipopolysaccharide (1µg/ml, as LPS used to mimic a bacterial infection) or metformin. Metformin stimulated expression of some Toll Like Receptors (TLR1-2; 2-1), but did not modify expression of the TLR4, known to be bound by LPS; as well as the increase in expression of some interleukins (IL-1β, IL-6, IL-8, IFN-y) after metformin stimulation and even more after an LPS and metformin exposure. In conclusion, modification of energy cell metabolism by metformin lead to activation of some set of immune system in the chicken Sertoli cells and even more after activation by bacterial component (LPS).